The ABC Model and its Applicability to Basal Angiosperms - Soltis, Douglas E. (Oxford University Press, 2007)
BACKGROUND: Although the flower is the central feature of the angiosperms, little is known of its origin and subsequent diversification. The ABC model has long been the unifying paradigm for floral developmental genetics, but it is based on phylogenetically derived eudicot models. Synergistic research involving phylogenetics, classical developmental studies, genomics and developmental genetics has afforded valuable new insights into floral evolution in general, and the early flower in particular. SCOPE AND CONCLUSIONS: Genomic studies indicate that basal angiosperms, and by inference the earliest angiosperms, had a rich tool kit of floral genes. Homologues of the ABCE floral organ identity genes are also present in basal angiosperm lineages; however, C-, E- and particularly B-function genes are more broadly expressed in basal lineages. There is no single model of floral organ identity that applies to all angiosperms; there are multiple models that apply depending on the phylogenetic position and floral structure of the group in question. The classic ABC (or ABCE) model may work well for most eudicots. However, modifications are needed for basal eudicots and, the focus of this paper, basal angiosperms. We offer ‘fading borders’ as a testable hypothesis for the basal-most angiosperms and, by inference, perhaps some of the earliest (now extinct) angiosperms.